Fournier gangrene - diagnostic and treatment - Beata Pilarska; Małgorzata Nartowicz; Aleksandra Jaworska-Czerwińska; Walery Zukow (Kazimierz Wielki University, 2018)
Fournier gangrene is a rare, progressively necrotizing perineum inflammation, often leading to death of the patient. The infection is caused by a mixed oxygen-anaerobic bacterial flora. Treatment is based on immediate and radical surgical intervention supported by antibiotic therapy and intensive general treatment. Adequate, quick adoption of curative and caring activities is one of the factors affecting the success of treatment. Depending on the dynamically progressing disease process, it is necessary to efficiently identify problems and modify treatment and nursing care plans from the stages of treatment.